2016
DOI: 10.1007/s00213-016-4351-5
|View full text |Cite
|
Sign up to set email alerts
|

Different effects of isolation-rearing and neonatal MK-801 treatment on attentional modulations of prepulse inhibition of startle in rats

Abstract: Isolation rearing impairs both baseline PPI and attentional modulations of PPI, but neonatally disrupting NMDA receptor-mediated transmissions specifically impair attentional modulations of PPI. Clozapine has limited alleviating effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 95 publications
0
15
0
Order By: Relevance
“…However, there is a strong body of literature in mammals, particularly in laboratory rodents, demonstrating that social deprivation causes dramatic effects on behavior [ 65 , 67 , 135 ], and some of the isolation-induced changes in behavior suggest that there may be underlying alterations in auditory processing. For example, social isolation alters the prepulse inhibition of the acoustic startle response in rodents, with isolated rats and mice generally showing an attenuated effect of prepulse stimuli compared to group-housed animals [ 136 , 137 , 138 , 139 , 140 , 141 , 142 ]. While most of this work has been conducted in males, there is evidence to suggest that the effect of prepulse inhibition is also attenuated in isolated females [ 143 ].…”
Section: Social Isolation and The Auditory Systemmentioning
confidence: 99%
“…However, there is a strong body of literature in mammals, particularly in laboratory rodents, demonstrating that social deprivation causes dramatic effects on behavior [ 65 , 67 , 135 ], and some of the isolation-induced changes in behavior suggest that there may be underlying alterations in auditory processing. For example, social isolation alters the prepulse inhibition of the acoustic startle response in rodents, with isolated rats and mice generally showing an attenuated effect of prepulse stimuli compared to group-housed animals [ 136 , 137 , 138 , 139 , 140 , 141 , 142 ]. While most of this work has been conducted in males, there is evidence to suggest that the effect of prepulse inhibition is also attenuated in isolated females [ 143 ].…”
Section: Social Isolation and The Auditory Systemmentioning
confidence: 99%
“…The acquired emotion information leads to an attentional bias to conditioned threat-associated stimuli in both humans and laboratory animals (Du, Li, Wu, & Li, 2009;Du, Wu, & Li, 2010Koster, Crombez, Van Damme, Verschuere, & De Houwer, 2005;Lei, Luo, Qu, Jia, & Li, 2014;Pischek-Simpson, Boschen, Neumann, & Waters, 2009; Z. Wu, Ding, Jia, & Li, 2016) and modulates neural activities in the auditory cortex and amygdala in both humans and laboratory animals (Armony, Quirk, & LeDoux, 1998;Du, Wang, Zhang, Wu, & Li, 2012;Morris et al, 2001;Morris, Öhman, & Dolan, 1998; for a recent review, see Grosso, Cambiaghi, Concina, Sacco, & Sacchetti, 2015).…”
mentioning
confidence: 99%
“…The failure of differentiating looming and receding sounds in isolation-reared rats may be related to their flawed attention (Li et al, 2009;Wu et al, 2018). Previously we found that isolation rearing abolished both fear conditioning-induced PPI enhancement (Du et al, 2010;Wu et al, 2016) and perceptual spatial separation-induced PPI enhancement (Du et al, 2009;Wu et al, 2016), which indicates an impairment of attending to the prepulse with acquired salient valence. Our study further extends it to show that isolation rearing abolished their attention to intrinsic salient value of prepulse (i.e., looming sounds) without acquisition.…”
Section: Discussionmentioning
confidence: 94%
“…Among the cognitive/behavioral deficits caused by isolation rearing, attentional impairment is found in several behavioral paradigms ( Wu et al, 2018 ). For example, it has been found that isolation rearing abolished both emotional and spatial attentional enhancements of PPI ( Du et al, 2009 , 2010 ; Li et al, 2009 ; Lim et al, 2012 ; Wu et al, 2016 ), declined attentional processing to novelty ( Atmore et al, 2020 ), and impaired attentional set shifting ( McLean et al, 2010 ). As looming sounds contain an intrinsic salient value for organism to avoid danger, it is of interest to investigate how isolation rearing would preserve or abolish this intrinsic attention to approaching objects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation